2014
DOI: 10.1186/cc13899
|View full text |Cite
|
Sign up to set email alerts
|

Serum cystatin C predicts vancomycin trough levels better than serum creatinine in hospitalized patients: a cohort study

Abstract: IntroductionSerum cystatin C can improve glomerular filtration rate (GFR) estimation over creatinine alone, but whether this translates into clinically relevant improvements in drug dosing is unclear.MethodsThis prospective cohort study enrolled adults receiving scheduled intravenous vancomycin while hospitalized at the Mayo Clinic in 2012. Vancomycin dosing was based on weight, serum creatinine with the Cockcroft-Gault equation, and clinical judgment. Cystatin C was later assayed from the stored serum used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 46 publications
2
61
1
2
Order By: Relevance
“…This biomarker shows promise for early detection and earlier intervention. Additionally, a study by Frazee et al[56] shows that biomarkers can also improve drug dosing. This study showed that vancomycin dosing in the ICU can be improved 2.5 fold when using cystatin C and serum creatinine to estimate GFR as opposed to just serum creatinine alone[56].…”
Section: Moving Towards Better Ade Preventionmentioning
confidence: 99%
“…This biomarker shows promise for early detection and earlier intervention. Additionally, a study by Frazee et al[56] shows that biomarkers can also improve drug dosing. This study showed that vancomycin dosing in the ICU can be improved 2.5 fold when using cystatin C and serum creatinine to estimate GFR as opposed to just serum creatinine alone[56].…”
Section: Moving Towards Better Ade Preventionmentioning
confidence: 99%
“…25) In addition, estimated GFR or Ccr calculated using cystatin C predicts vancomycin trough levels better than Ccr calculated by Cockcroft-Gault formula. 26,27) In fact, the mean estimated GFR (69.1±33.1 mL/min) 26) or Ccr (46.6±24.6 mL/min) 27) calculated using cystatin C levels before DRPM administration tended to be lower than the mean Ccr calculated by Cockcroft-Gault formula (76.0±37.4 mL/min). Thus, the dosage regimen of DRPM, a renally excreted drug, for ICU patients may need to be also established by stratifying renal function based on GFR or Ccr estimated using cystatin C.…”
Section: Discussionmentioning
confidence: 94%
“…Les é tudes sur la pré diction de la clairance de mé dicaments (le plus souvent les aminoglycosides et la vancomycine) par les diffé rentes é quations sont plus rares et les ré sultats contradictoires [48,51,58,76,[84][85][86][87][88][89]. Enfin, une autre façon d'illustrer les é ventuelles discordances entre les é quations est de reprendre des donné es d'é tudes cliniques observationnelles ou interventionnelles et de vé rifier si les conclusions des dites é tudes resteraient identiques en utilisant l'é quation de Cockcroft (comme cela a é té fait de prime abord dans la plupart des é tudes) ou une autre é quation.…”
Section: Le Choix De La Formule : Que Nous Dit La Litte´rature ?unclassified
“…Notons é galement que des é tudes commencent à être publié es sur l'inté rêt de nouveaux biomarqueurs, le plus avancé é tant la cystatine C [83,84,88,89,110].…”
Section: Conclusion Et Propositionsunclassified